The ability of indigenous Bacillus spp. consortia to control the anthracnose disease (Colletrotricum capsici) and increase the growth of chili plants - Yulmira Yanti; HASMIANDY HAMID; REFLIN; WARNITA; TRIMURTI HABAZAR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Yanti Y, Hamid H, Reflin, Warnita, Habazar T. 2019. The ability of indigenous Bacillus spp. consortia to control the anthracnose disease (Colletrotricum capsici) and increase the growth of chili. Biodiversitas 21: 179-186. Anthracnose disease caused by Colletotrichum capsici can reduce yields of chili up to 80%. The control of anthracnose disease is generally carried out using synthetic fungicides. However, the use of these fungicides can pollute the environment and harm human health. One alternative control that needs to be developed is the use of Bacillus spp. as a biocontrol agent. The study was conducted to obtain an indigenous Bacillus spp. consortium that compatible as a biological agent for the control of the anthracnose diseases and promoting the growth of chili plants. The experiment was arranged as a completely randomized design, consisted of three stages, namely: 1) inhibitory test of indigenous Bacillus spp. against C. capsici in vitro, 2) compatibility test of indigenous Bacillus spp. and 3) Test of indigenous Bacillus spp.consortium for controlling C. capsici and promoting the growth of chili. The results showed that eight species of indigenous endophytic bacteria could inhibit the growth of C. capsici in vitro. All combinations of indigenous Bacillus spp. were compatible for controlling C. capsici. Four combinations of Bacillus spp. were able to increase the growth of chili plants. K1 consortium (Bacillus pseudomycoides strain SLBE 3.1 AP, Bacillus thuringiensis strain SLBE 2.3 BB, Bacillus toyonensis strain AGBE 2.1 TL) was the best consortium for controlling C. capsici.